2017
DOI: 10.1186/s13089-017-0071-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in trauma: a nation-wide cross-sectional investigation

Abstract: BackgroundThe Focused Assessment with Sonography in Trauma (FAST) protocol is considered beneficial in emergent evaluation of trauma patients with blunt or penetrating injury and has become integrated into the Advanced Trauma Life Support (ATLS) protocol. No guidelines exist as to the use of ultrasonography in trauma in Denmark. We aimed to determine the current use of ultrasonography for assessing trauma patients in Denmark.MethodsWe conducted a nation-wide cross-sectional investigation of ultrasonography usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(22 reference statements)
0
3
1
Order By: Relevance
“…2 and 3) which will help in early detection of small pneumothoraces. In contrast with other studies [5, 18], our study has shown that the lateral sites had the least probabilities for the presence of air pockets. Moreover, the presence of air at these sites indicates large pneumothorax volume (more than 500 mL).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…2 and 3) which will help in early detection of small pneumothoraces. In contrast with other studies [5, 18], our study has shown that the lateral sites had the least probabilities for the presence of air pockets. Moreover, the presence of air at these sites indicates large pneumothorax volume (more than 500 mL).…”
Section: Discussioncontrasting
confidence: 99%
“…This method is time-consuming and less practical in trauma setting as it wastes a critical time needed for the management of other serious injuries. Other studies, based on the assumption that air will accumulate anteriorly in supine patients, have recommended US scanning the chest in one or two positions: either anterior at the second intercostal space in the midclavicular line [16, 17] and/or at the anterolateral chest wall at the 4th or 5th intercostal space at midaxillary line [5, 18].…”
Section: Discussionmentioning
confidence: 99%
“…This idea can be extended for AR rare pathogenic missense variants. Here, random clusters may support the identification of critical molecular regions 33 , 34 . For VPS13B no clustering of neither loss-of-function nor missense variants could be recognized so far 8 .…”
Section: Introductionmentioning
confidence: 73%
“…It is useful in providing rapid and noninvasive evaluation for pneumothorax [30,31], pulmonary edema [32], atelectasis, effusion, and pneumonia. It has been demonstrated to be useful in a prehospital setting as well as intraoperatively during a polytrauma surgery [33]. Given its small size and portability, POCUS has been utilized in both helicopter and military settings to diagnose pneumothorax (PTX) [34,35].…”
Section: Key Pointsmentioning
confidence: 99%